Implementation of Law Against Criminal Actions of State Civil Servants In The Election of Governor North Maluku - Hasmiah Hamid (International Journal of Education, Information Technology, and Others, 2020)
This study aims to describe the application of the law to criminal acts in the general election for the Governor and Deputy Governor of North Maluku by the State Civil Apparatus (ASN). Based on the data that the author has obtained in one of the areas of the Tidore Islands City Election Supervisory Agency, it can be concluded that the application of the law to the crime of election for the Governor and Deputy Governor of North Maluku through the recommendations of the findings of the Tidore Islands City Election Supervisory Agency, Number: 13 / TM / PG / Kot / 32.02 / X / 2018, it is appropriate to use Article 80 with reference to the Pilkada criminal sanctions as stipulated in Article 116 paragraph (4), Law No. 32 of 2004 concerning Regional Government which reads: Every state official, structural and functional official in a state office and a village head who deliberately violates the provisions referred to in article 80 shall be punished with imprisonment for a minimum of 1 (one) month or a maximum of 6 (six). month and / or a fine of at least Rp. 600,000 or a maximum of Rp. 6,000,000. In addition, there are several law enforcement officers who are not ready to be professional and committed to implementing regulations related to criminal acts related to regional head elections committed by the State Civil Apparatus.